Al / PDA / CuZnO2 / AP composite energetic material and preparation method thereof

The bimetallic nanocatalyst CuZnO2 and PDA layers prepared by using chemical precipitation method in composite solid propellants, and the Al/PDA/CuZnO2/AP composite energy-containing materials were prepared in combination with cooling and recrystallization method, which solved the contact between the catalyst and the oxidant and the metal combustion agent. The problem of excessive distance has achieved efficient thermal decomposition and combustion efficiency, and the particle size distribution is uniform, which is suitable for the application of composite solid propellants.

CN119490375APending Publication Date: 2025-02-21NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714356.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Among the existing composite solid propellants, the contact distance between the catalyst and the oxidant and the metal combustion agent is too large, resulting in slow mass and heat transfer rates, and poor particle size grading, which cannot meet the needs of loading density and mechanical properties.

Method used

The bimetallic nanocatalyst CuZnO2 was prepared by chemical precipitation method, and the bimetal nanocatalyst CuZnO2 was introduced to make it evenly adhered to the surface of Al powder by introducing PDA. The Al/PDA/CuZnO2/AP composite energy-containing material with controllable particle size was prepared by cooling and recrystallization method to realize metal combustion Oriented arrangement of agents, catalysts and oxidants self-assemble.

Benefits of technology

The catalyst is in close contact with the oxidant and the metal combustion agent, which improves the thermal decomposition efficiency and combustion efficiency of the composite particles, and has a uniform particle size distribution and a regular morphology, which is suitable for the application of composite solid propellants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490375A_ABST
    Figure CN119490375A_ABST
Patent Text Reader

Abstract

The invention discloses an Al / PDA / CuZnO2 / AP composite energetic material, which is characterized in that PDA is used as an interface bonding layer to enable Al powder to be in close contact with a bimetallic catalyst CuZnO2 and AP, nano-particles CuZnO2 are uniformly attached to the PDA modified Al powder, and the Al powder, the CuZnO2 and the AP are directionally arranged and self-assembled to form an energetic micro-unit with Al / PDA / CuZnO2 as a core and AP as a shell layer. According to the preparation method of the composite energetic material, a mixed solvent is selected as a crystallization solvent, the Al / PDA / CuZnO2 / AP composite energetic material with the controllable particle size is prepared through a cooling recrystallization method, the grading requirement of a composite solid propellant is met, the metal combustion agent, the catalyst and the oxidizing agent are tightly combined, the reaction diffusion distance of the metal combustion agent, the catalyst and the oxidizing agent is shortened, and therefore the particle size controllable Al / PDA / CuZnO2 / AP composite energetic material is obtained. The synergistic energy release effect is improved, and the energy performance of the composite solid propellant is expected to be enhanced. The preparation method is simple and easy to operate, the crystallization solvent can be recycled for multiple times, and the preparation method has the characteristics of environmental protection and high economic benefit and is beneficial to industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and relates to a composite energetic material for composite solid propellant, and specifically to an Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof. Background Art

[0002] Composite solid propellant is an energetic mixed material with specific properties, mainly composed of an oxidizer and a metal combustion agent. Oxidizer AP is widely used due to its high oxygen content, large formation enthalpy, good stability, and good compatibility with other components in the propellant; metal fuel Al powder has been widely used in composite solid propellants due to its high combustion calorific value, high density and low cost. In composite solid propellants, the thermal decomposition temperature of AP and the combustion efficiency of Al powder affect the energy performance of the propellant, which is often improved by adding catalysts or constructing energetic composite micro-units to make AP and Al powder in close contact. For example, J.Lyu et al. used spray drying technology in the article "Thermal decomposition and combustion behavior of the core-shell Al@AP composite embedded with CuO as a catalyst" [J] Fuel 356 (2024)129587 to coat Al particles with AP and embed a trace amount of CuO in the core-shell structure. The prepared Al@AP / CuO has a size of about 20 μm. Compared with traditional mixtures, the thermal decomposition of Al@AP / CuO is enhanced and the combustion efficiency is improved.

[0003] Catalysts are very important for regulating the burning rate of composite solid propellants. Currently, the commonly used catalysts are mainly transition state single metals and their oxides, and bimetallic catalysts are less studied. The catalytic activity of the catalyst is crucial to the interfacial contact with other components. If the contact distance between the catalyst and the oxidant and the metal combustion agent is too large, the mass transfer and heat transfer rates will be slow. The particle size distribution in the composite solid propellant affects the packing density and mechanical properties. The particle size of the composite particles prepared by the solvent-antisolvent method, electrostatic spray method and supercritical flow method is generally less than 30 μm. The composite particles prepared by the solvent evaporation method and the deposition method have poor morphology regularity and cannot meet the grading requirements.

[0004] Therefore, it is of great significance to develop a multi-component composite energetic material that can achieve directional arrangement, uniform and tight combination of metal combustion agent, catalyst and oxidant, as well as complete coating, regular morphology and controllable particle size. Summary of the invention

[0005] In order to solve the above problems, the present invention discloses an Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof, wherein a bimetallic nanocatalyst CuZnO2 is prepared by a chemical precipitation method, and PDA with high compatibility, high adhesion and high interfacial activity is introduced to make CuZnO2 uniformly adhere to the surface of Al powder. A mixed solvent is selected as a crystallization solvent, and a quasi-spherical Al / PDA / CuZnO2 / AP composite energetic material with controllable particle size and uniform distribution is prepared by a cooling recrystallization method, and the metal combustion agent Al powder, the catalyst CuZnO2 and the oxidant AP are arranged and self-assembled in a directional manner to form an energetic micro-unit with Al / PDA / CuZnO2 as the core and AP as the shell.

[0006] To achieve the above object, the technical solution of the present invention is as follows: The invention discloses an Al / PDA / CuZnO2 / AP composite energetic material. PDA is used as an interface bonding layer to make Al powder in close contact with bimetallic catalysts CuZnO2 and AP. Nanoparticle CuZnO2 is uniformly attached to the PDA-modified Al powder. The directional arrangement of Al powder, CuZnO2 and AP is self-assembled to form energetic micro-units with Al / PDA / CuZnO2 as the core and AP as the shell.

[0007] As an improvement of the present invention, the composite energetic material has a spherical morphology and a particle size of 10-350 μm, and the mass fractions of the metal combustion agent Al powder, the polymer PDA, the catalyst CuZnO2 and the oxidant AP are 10%-70%, 1%-10%, 1%-5% and 30%-90% respectively.

[0008] The present invention also provides a method for preparing an Al / PDA / CuZnO2 / AP composite energetic material, comprising the following steps: S1. Preparation of Al / PDA: dissolve dopamine hydrochloride in a TRIS buffer solution at pH=8.5, add Al powder after it is completely dissolved, and stir magnetically under water bath heating to react; dopamine self-polymerizes on the surface of Al powder to form polydopamine through a pH-induced oxidation process; Al / PDA particles are obtained after centrifugation, washing, and vacuum drying; S2. Preparation of Al / PDA / CuZnO2: Dissolve copper acetate and zinc acetate in deionized water respectively, transfer the solution to a beaker after complete dissolution, and add glacial acetic acid; then transfer the mixture solution to a round-bottom flask, heat it to liquid reflux under stirring conditions, and add NaOH after the color of the solution changes from blue to dark green; continue heating and stirring, and stop heating after the color of the solution changes from dark green to brown-black, and add Al / PDA particles after cooling to room temperature; disperse CuZnO2 evenly under stirring conditions, and attach CuZnO2 to the surface of Al / PDA particles with the help of the viscosity of PDA; obtain Al / PDA / CuZnO2 composite particles after centrifugation, washing, and vacuum drying.

[0009] S3. Preparation of Al / PDA / CuZnO2 / AP: prepare a mixed solvent of organic solvent and water in a certain volume ratio, dissolve AP in the mixed solvent, control the temperature of the water bath to obtain AP high-temperature solution and AP low-temperature solution; disperse Al / PDA / CuZnO2 composite particles in the AP low-temperature solution, add AP high-temperature solution dropwise thereto under stirring conditions, age and grow crystals, filter and vacuum dry to obtain Al / PDA / CuZnO2 / AP composite energetic material.

[0010] As an improvement of the present invention, in step S1, the particle size of the Al powder is 500 nm to 30 μm.

[0011] As an improvement of the present invention, in step S1, the heating temperature is 20-50°C, the magnetic stirring speed is 100-2000 rpm; the centrifugation time is 3-10 min, the speed is 2000-5000 rpm, and the washing is three times each with water and ethanol.

[0012] As an improvement of the present invention, in step S2, the heating temperature is 70-150°C, the magnetic stirring speed is 100-1000 rpm; the centrifugation time is 5-10 min, the speed is 3000-6000 rpm, and the washing is three times each with water and ethanol.

[0013] As an improvement of the present invention, in step S3, the organic solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, methanol, ethanol, acetonitrile, N-methylpyrrolidone, and dimethyl sulfoxide.

[0014] As an improvement of the present invention, in step S3, the volume ratio of the organic solvent to water is 1:1 to 1:20.

[0015] As an improvement of the present invention, in step S3, the temperature of the AP high temperature solution is 30-100°C, and the temperature of the AP low temperature solution is 0-30°C.

[0016] As an improvement of the present invention, in step S3, the stirring rate is 50-1000 rpm, the dropping rate is 1-20 mL / min, and the aging crystal growth time is 1-12 h.

[0017] The present invention adopts an in-situ polymerization method to form a dense PDA layer on the surface of Al powder to obtain Al / PDA particles; then a chemical precipitation method is adopted to prepare a bimetallic nanocatalyst CuZnO2 and make it evenly adhere to the surface of Al / PDA to form Al / PDA / CuZnO2 composite particles; finally, a mixed solvent is selected as a crystallization solvent, and a cooling recrystallization method is adopted to prepare the Al / PDA / CuZnO2 / AP composite energetic material.

[0018] The beneficial effects of the present invention are: (1) The present invention prepares the bimetallic nanocatalyst CuZnO2 by chemical precipitation method, and the preparation method is simple and easy to operate. Experimental data show that the bimetallic nanocatalyst CuZnO2 can further accelerate the thermal decomposition of the composite particles. CuZnO2, as an intermediate layer, is in close contact with Al powder and AP, which can not only catalyze the decomposition of AP, but also form a thermite with Al powder to improve the combustion efficiency of aluminum powder.

[0019] (2) The Al / PDA / CuZnO2 / AP prepared by the present invention is an energetic microunit with Al / PDA / CuZnO2 as the core and AP as the shell, which is completely coated, has a uniform particle size distribution, and has good sphericity. The directional arrangement of the metal combustion agent, the catalyst, and the oxidant are uniformly and tightly combined, shortening the reaction diffusion distance of the three. Al / PDA / CuZnO2 can catalyze the thermal decomposition of AP, and the accelerated decomposition of AP enhances the reaction of Al and CuZnO2. The two promote each other and improve the synergistic energy release effect.

[0020] (3) The cooling recrystallization method of the present invention uses an organic solvent and water as a mixed solvent. By adjusting the type of organic solvent and the ratio of organic solvent to water, the particle size and morphology of the Al / PDA / CuZnO2 / AP composite energetic material can be adjusted within a certain range, and a spherical composite energetic material with controllable particle size can be obtained.

[0021] (4) The present invention adopts the cooling recrystallization method to prepare Al / PDA / CuZnO2 / AP composite energetic materials, which has low requirements on laboratory equipment and simple operation method. The crystallization solvent can be recycled many times, which is green, environmentally friendly and economically efficient, and is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a SEM image of Al / PDA particles during the preparation process of Example 1 of the present invention; Figure 2is a SEM image of Al / PDA / CuZnO2 composite particles during the preparation process of Example 1 of the present invention; Figure 3 This is a SEM image of the Al / PDA / CuZnO2 / AP composite energetic material prepared in Example 1 of the present invention; Figure 4 This is the DSC graph of the Al / PDA / CuZnO2 / AP composite energetic material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The materials, reagents, instruments, etc. used in the examples are all commercially available unless otherwise specified. It should be understood that the embodiments described herein are only a part of the embodiments of the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments of the changes or replacements of the experimental steps and conditions of the present invention belong to the protection scope of the present invention.

[0024] The technical idea of ​​the present invention is: PDA is selected as an interface layer to modify the surface of Al powder, and its strong adhesion is used to make the bimetallic nanocatalyst CuZnO2 uniformly adhere to the PDA-modified Al powder. A fully coated Al / PDA / CuZnO2 / AP composite energetic material is prepared by a mixed solvent cooling and recrystallization method to achieve directional arrangement of metal combustion agents, catalysts and oxidants, uniform and tight combination, shorten the reaction diffusion distance of the three, and improve the synergistic energy release effect. Composite energetic materials with different particle sizes and morphologies can also be obtained by adjusting the type of organic solvent and the ratio of organic solvent to water.

[0025] According to the above technical ideas, specific embodiments of the present invention are given below.

[0026] Example 1 An Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof are prepared according to the following steps: (1) Preparation of Al / PDA: 1 g of dopamine hydrochloride was dissolved in a TRIS buffer solution at pH = 8.5. After complete dissolution, 10 g of 4 μm Al powder was added and heated in a water bath at 28°C with magnetic stirring at a speed of 600 rpm to react. Through the pH-induced oxidation process, dopamine self-polymerized on the surface of the Al powder to form polydopamine. Al / PDA / CuZnO2 composite particles were obtained after centrifugation (5000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0027] (2) Preparation of Al / PDA / CuZnO2: Dissolve 2.5 g of copper acetate and 2.74 g of zinc acetate in 50 mL of deionized water respectively. After complete dissolution, transfer the solution to a beaker and add 1 mL of glacial acetic acid. Then transfer the mixture solution to a round-bottom flask and heat it to liquid reflux under stirring conditions. After the color of the solution changes from blue to dark green, add 0.5 g of NaOH. Continue heating and stirring. Stop heating after the color of the solution changes from dark green to brown-black. After cooling to room temperature, add Al / PDA particles. Disperse CuZnO2 evenly under stirring conditions. CuZnO2 adheres to the surface of Al / PDA particles with the help of the viscosity of PDA. Centrifuge (6000 rpm, 5 min), wash with water and ethanol, and vacuum dry to obtain Al / PDA / CuZnO2 composite particles.

[0028] (3) Preparation of Al / PDA / CuZnO2 / AP: Prepare a mixed solvent of N,N-dimethylformamide and water with a volume ratio of 1:5, and dissolve AP in the mixed solvent. By controlling the temperature of the water bath, a high-temperature AP solution of 70°C and a low-temperature AP solution of 10°C are obtained. Al / PDA / CuZnO2 composite particles are dispersed in the low-temperature AP solution, and the high-temperature AP solution is added dropwise at a stirring rate of 300 rpm at a dropping rate of 10 mL / min. The crystals are aged for 3 h, filtered, and vacuum dried to obtain the Al / PDA / CuZnO2 / AP composite energetic material.

[0029] Figure 1 This is the SEM image of Al / PDA particles during the preparation process. The Al / PDA particles are evenly dispersed, the surface of the smooth Al powder particles is evenly covered with the PDA layer, and the particle size of the Al / PDA particles is 3~6μm.

[0030] Figure 2 This is the SEM image of the Al / PDA / CuZnO2 composite particles during the preparation process. It can be clearly seen that the nanoparticles CuZnO2 are evenly attached to the PDA-modified Al powder.

[0031] Figure 3 The SEM image of the prepared Al / PDA / CuZnO2 / AP composite energetic material shows that its morphology is spherical, with a particle size of about 200 μm and uniform distribution. Al / PDA / CuZnO2 is wrapped in AP, forming a core-shell structure with Al / PDA / CuZnO2 as the core and AP as the shell.

[0032] Figure 4The DSC diagram of the prepared Al / PDA / CuZnO2 / AP composite energetic material shows that the endothermic peak at 245.0℃ is the crystal transformation peak of AP from orthorhombic to cubic, and the endothermic peak at 662.0℃ is caused by the melting of Al peak. It can be seen from the figure that after AP coated Al powder, the high and low temperature decomposition peaks of AP merged into one, and the addition of bimetallic nanocatalyst CuZnO2 brought the decomposition peak of AP forward. Compared with the simple mixture of Al and AP, Al / PDA / AP sample, and the simple mixture of Al / PDA / AP and CuZnO2, the decomposition peak temperature of Al / PDA / CuZnO2 / AP was advanced by 92.5℃, 54.9℃, and 37.1℃, respectively, and the heat release increased by 746.43 J / g, 228.5 J / g, and 130.4 J / g, respectively. This is because Al powder, CuZnO2, and AP are closely combined, shortening the reaction diffusion distance of the three and improving the synergistic energy release effect.

[0033] Example 2 An Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof are prepared according to the following steps: (1) Preparation of Al / PDA: 1 g of dopamine hydrochloride was dissolved in a TRIS buffer solution at pH = 8.5. After complete dissolution, 10 g of 14 μm Al powder was added and heated in a water bath at 28 °C with magnetic stirring to react at a speed of 600 rpm. Through the pH-induced oxidation process, dopamine self-polymerized on the surface of the Al powder to form polydopamine. Al / PDA composite particles were obtained after centrifugation (5000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0034] (2) Preparation of Al / PDA / CuZnO2: Dissolve 2.5 g of copper acetate and 2.74 g of zinc acetate in 50 mL of deionized water respectively. After complete dissolution, transfer the solution to a beaker and add 1 mL of glacial acetic acid. Then transfer the mixture solution to a round-bottom flask and heat it to liquid reflux under stirring conditions. After the color of the solution changes from blue to dark green, add 0.5 g of NaOH. Continue heating and stirring. Stop heating after the color of the solution changes from dark green to brown-black. After cooling to room temperature, add Al / PDA particles. Disperse CuZnO2 evenly under stirring conditions. CuZnO2 adheres to the surface of Al / PDA particles with the help of the viscosity of PDA. Centrifuge (6000 rpm, 5 min), wash with water and ethanol, and vacuum dry to obtain Al / PDA / CuZnO2 composite particles.

[0035] (3) Preparation of Al / PDA / CuZnO2 / AP: Prepare a mixed solvent of N,N-dimethylformamide and water with a volume ratio of 1:10, and dissolve AP in the mixed solvent. By controlling the temperature of the water bath, a high-temperature AP solution of 70°C and a low-temperature AP solution of 10°C were obtained. Al / PDA / CuZnO2 composite particles were dispersed in the low-temperature AP solution, and the high-temperature AP solution was added dropwise at a stirring rate of 300 rpm at a rate of 8 mL / min. The particles were aged for 2 h, filtered, and vacuum dried to obtain the Al / PDA / CuZnO2 / AP composite energetic material.

[0036] Example 3 An Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof are prepared according to the following steps: (1) Preparation of Al / PDA: 1 g of dopamine hydrochloride was dissolved in a TRIS buffer solution at pH = 8.5. After complete dissolution, 20 g of 4 μm Al powder was added and heated in a water bath at 25 °C with magnetic stirring to react at a speed of 300 rpm. Through the pH-induced oxidation process, dopamine self-polymerized on the surface of the Al powder to form polydopamine. Al / PDA composite particles were obtained after centrifugation (5000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0037] (2) Preparation of Al / PDA / CuZnO2: Dissolve 2.5 g of copper acetate and 2.74 g of zinc acetate in 50 mL of deionized water respectively. After complete dissolution, transfer the solution to a beaker and add 1 mL of glacial acetic acid. Then transfer the mixture solution to a round-bottom flask and heat it to liquid reflux under stirring conditions. After the color of the solution changes from blue to dark green, add 1 g of NaOH. Continue heating and stirring. Stop heating after the color of the solution changes from dark green to brown-black. After cooling to room temperature, add Al / PDA particles. Disperse CuZnO2 evenly under stirring conditions. With the help of the viscosity of PDA, CuZnO2 adheres to the surface of Al / PDA particles. Centrifuge (5000 rpm, 6 min), wash with water and ethanol, and vacuum dry to obtain Al / PDA / CuZnO2 composite particles.

[0038] (3) Preparation of Al / PDA / CuZnO2 / AP: Prepare a mixed solvent of N,N-dimethylformamide and water with a volume ratio of 1:10, and dissolve AP in the mixed solvent. By controlling the temperature of the water bath, a 70 ℃ AP high-temperature solution and a 10 ℃ AP low-temperature solution were obtained. Al / PDA / CuZnO2 composite particles were dispersed in the AP low-temperature solution, and the AP high-temperature solution was added dropwise at a stirring rate of 500 rpm at a dropping rate of 10 mL / min. The crystals were aged for 3 h, filtered, and vacuum dried to obtain the Al / PDA / CuZnO2 / AP composite energetic material.

[0039] Example 4 An Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof are prepared according to the following steps: (1) Preparation of Al / PDA: 1 g of dopamine hydrochloride was dissolved in a TRIS buffer solution at pH = 8.5. After complete dissolution, 10 g of 29 μm Al powder was added and heated in a water bath at 28°C with magnetic stirring at a speed of 600 rpm. Through the pH-induced oxidation process, dopamine self-polymerized on the surface of the Al powder to form polydopamine. Al / PDA composite particles were obtained after centrifugation (5000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0040] (2) Preparation of Al / PDA / CuZnO2: Dissolve 2.5 g of copper acetate and 2.74 g of zinc acetate in 50 mL of deionized water respectively. After complete dissolution, transfer the solution to a beaker and add 1 mL of glacial acetic acid. Then transfer the mixture solution to a round-bottom flask and heat it to liquid reflux under stirring conditions. After the color of the solution changes from blue to dark green, add 0.5 g of NaOH. Continue heating and stirring. Stop heating after the color of the solution changes from dark green to brown-black. After cooling to room temperature, add Al / PDA particles. Disperse CuZnO2 evenly under stirring conditions. CuZnO2 adheres to the surface of Al / PDA particles with the help of the viscosity of PDA. Centrifuge (6000 rpm, 5 min), wash with water and ethanol, and vacuum dry to obtain Al / PDA / CuZnO2 composite particles.

[0041] (3) Preparation of Al / PDA / CuZnO2 / AP: Prepare a mixed solvent of N,N-diethylformamide and water with a volume ratio of 1:15, and dissolve AP in the mixed solvent. By controlling the temperature of the water bath, a high-temperature AP solution of 60°C and a low-temperature AP solution of 10°C were obtained. Al / PDA / CuZnO2 composite particles were dispersed in the low-temperature AP solution, and the high-temperature AP solution was added dropwise at a stirring rate of 500 rpm at a rate of 5 mL / min. The crystals were aged for 1 h, filtered, and vacuum dried to obtain the Al / PDA / CuZnO2 / AP composite energetic material.

[0042] Example 5 An Al / PDA / CuZnO2 / AP composite energetic material and a preparation method thereof are prepared according to the following steps: (1) Preparation of Al / PDA: 1 g of dopamine hydrochloride was dissolved in a TRIS buffer solution at pH = 8.5. After complete dissolution, 10 g of 4 μm Al powder was added and heated in a water bath at 25°C with magnetic stirring to react at a speed of 400 rpm. Through the pH-induced oxidation process, dopamine self-polymerized on the surface of the Al powder to form polydopamine. Al / PDA composite particles were obtained after centrifugation (5000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0043] (2) Preparation of Al / PDA / CuZnO2: Dissolve 1.25 g of copper acetate and 1.37 g of zinc acetate in 50 mL of deionized water respectively. After complete dissolution, transfer the solution to a beaker and add 1 mL of glacial acetic acid. Then transfer the mixture solution to a round-bottom flask and heat it to liquid reflux under stirring conditions. After the color of the solution changes from blue to dark green, add 0.5 g of NaOH. Continue heating and stirring. Stop heating after the color of the solution changes from dark green to brown-black. After cooling to room temperature, add Al / PDA particles. Disperse CuZnO2 evenly under stirring conditions. CuZnO2 adheres to the surface of Al / PDA particles with the help of the viscosity of PDA. Al / PDA / CuZnO2 composite particles are obtained after centrifugation (6000 rpm, 5 min), washing with water and ethanol, and vacuum drying.

[0044] (3) Preparation of Al / PDA / CuZnO2 / AP: Prepare a mixed solvent of N-methylpyrrolidone and water with a volume ratio of 1:10, and dissolve AP in the mixed solvent. By controlling the temperature of the water bath, a high-temperature AP solution of 70 ℃ and a low-temperature AP solution of 10 ℃ were obtained. Al / PDA / CuZnO2 composite particles were dispersed in the low-temperature AP solution, and the high-temperature AP solution was added dropwise at a stirring rate of 300 rpm at a dropping rate of 12 mL / min. The crystals were aged for 5 h, filtered, and vacuum dried to obtain the Al / PDA / CuZnO2 / AP composite energetic material.

[0045] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made on the basis of the above embodiments without departing from the principles of the present invention. These improvements and modifications all fall within the scope of protection of the claims of the present invention.

Claims

1. An Al / PDA / CuZnO2 / AP composite energetic material, characterized in that: PDA acts as an interfacial bonding layer to bring Al powder into close contact with the bimetallic catalysts CuZnO2 and AP. Nanoparticles of CuZnO2 are uniformly attached to the PDA-modified Al powder. The directional arrangement of Al powder, CuZnO2 and AP self-assembles to form energetic microunits with Al / PDA / CuZnO2 as the core and AP as the shell.

2. The Al / PDA / CuZnO2 / AP composite energetic material according to claim 1, characterized in that: The composite energetic material has a spherical shape and a particle size of 10-350 μm. The mass fractions of the metal combustion agent Al powder, the polymer PDA, the catalyst CuZnO2 and the oxidant AP are 10%-70%, 1%-10%, 1%-5% and 30%-90% respectively.

3. A method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to any one of claims 1-2, characterized in that: The steps include: S1. Preparation of Al / PDA: dissolve dopamine hydrochloride in a TRIS buffer solution at pH=8.5, add Al powder after it is completely dissolved, and stir magnetically under water bath heating to react; dopamine self-polymerizes on the surface of Al powder to form polydopamine through a pH-induced oxidation process; Al / PDA particles are obtained after centrifugation, washing, and vacuum drying; S2. Preparation of Al / PDA / CuZnO2: Dissolve copper acetate and zinc acetate in deionized water respectively, transfer the solution to a beaker after complete dissolution, and add glacial acetic acid; then transfer the mixture solution to a round-bottom flask, heat it to liquid reflux under stirring conditions, and add NaOH after the color of the solution changes from blue to dark green; continue heating and stirring, stop heating after the color of the solution changes from dark green to brown-black, and add Al / PDA particles after cooling to room temperature; disperse CuZnO2 evenly under stirring conditions, and CuZnO2 adheres to the surface of Al / PDA particles with the help of the viscosity of PDA; obtain Al / PDA / CuZnO2 composite particles after centrifugation, washing, and vacuum drying; S3. Preparation of Al / PDA / CuZnO2 / AP: prepare a mixed solvent of organic solvent and water in a certain volume ratio, dissolve AP in the mixed solvent, control the temperature of the water bath to obtain AP high-temperature solution and AP low-temperature solution; disperse Al / PDA / CuZnO2 composite particles in the AP low-temperature solution, add AP high-temperature solution dropwise thereto under stirring conditions, age and grow crystals, filter and vacuum dry to obtain Al / PDA / CuZnO2 / AP composite energetic material.

4. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In the step S1, the particle size of the Al powder is 500 nm to 30 μm.

5. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In the step S1, the heating temperature is 20-50°C, the magnetic stirring speed is 100-2000 rpm; the centrifugation time is 3-10 min, the speed is 2000-5000 rpm, and the washing is three times each with water and ethanol.

6. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In the step S2, the heating temperature is 70-150°C, the magnetic stirring speed is 100-1000 rpm; the centrifugation time is 5-10 min, the speed is 3000-6000 rpm, and the washing is three times each with water and ethanol.

7. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In the step S3, the organic solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform, methanol, ethanol, acetonitrile, N-methylpyrrolidone and dimethyl sulfoxide.

8. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In step S3, the volume ratio of the organic solvent to water is 1:1 to 1:

20.

9. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In step S3, the temperature of the AP high temperature solution is 30-100°C, and the temperature of the AP low temperature solution is 0-30°C.

10. The method for preparing the Al / PDA / CuZnO2 / AP composite energetic material according to claim 3, characterized in that: In the step S3, the stirring rate is 50-1000 rpm, the dropping rate is 1-20 mL / min, and the aging crystal growth time is 1-12 h.